(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
The article covers the methods, principles of asynchronous teaching of the second law of thermodynamics. On the basis of asynchronous teaching, full coverage of the topic and technologies for the formation of science-based compensation in students were revealed